Shipping cost and development of the landlocked developing countries: Panel evidence from the common correlated effects approach. (12th February 2020) - Pham, Ngoc Thien Anh; Sim, Nicholas
Abstract: We estimate the impact of shipping cost on development for landlocked developing countries (LLDCs). Since container trade is important to them, we construct a country‐specific measure of shipping cost, called HarpexCost, which combines the global cost of container shipping with information on how exposed to container shipping each LLDC is. We employ the common correlated effects (CCE) estimator of Pesaran ( Econometrica, 2006; 55: 967) to first estimate the impact of HarpexCost on the LLDCs' development, and then recover the actual impact of shipping cost from these estimates. Overall, we observe that shipping cost has large negative effects on the LLDCs. Building upon these results, we provide new estimates on the cost of landlockedness and how trade benefits their development.